1995
DOI: 10.1007/bf02187185
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress in cerebral arteries supplying arteriovenous malformations

Abstract: Arteries supplying cerebral arteriovenous malformations (AVMs) are known to dilate with time. These changes are reversible, and the feeders have been shown to slowly decrease in calibre after removal of the AMV. There is evidence that arteries alter their internal diameters in response to sustained changes of blood flow so that shear stress is kept constant. This implies that blood flow-induced shear stress might be the driving force for remodelling of the cerebral vascular network in the presence of an AVM, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…4 The first and only other study to measure WSS in patients with cerebral AVMs was published by Rossitti and Svendsen in 1995. 12 They calculated WSS in a total of 17 feeder arteries in 15 patients (27% with hemorrhagic presentation) by obtaining blood flow velocity within the principal feeder arteries (anterior, middle, and posterior cerebral arteries) and their normal contralateral counterparts (also anterior, middle, and posterior cerebral arteries) using transcranial Doppler ultrasound (TCD) and assessing vessel size from digital subtraction angiography. They found that mean vessel caliber was significantly larger within the AVM feeder arteries compared with the corresponding arteries in the contralateral hemisphere (0.14 cm versus 0.12 cm; P=0.0008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The first and only other study to measure WSS in patients with cerebral AVMs was published by Rossitti and Svendsen in 1995. 12 They calculated WSS in a total of 17 feeder arteries in 15 patients (27% with hemorrhagic presentation) by obtaining blood flow velocity within the principal feeder arteries (anterior, middle, and posterior cerebral arteries) and their normal contralateral counterparts (also anterior, middle, and posterior cerebral arteries) using transcranial Doppler ultrasound (TCD) and assessing vessel size from digital subtraction angiography. They found that mean vessel caliber was significantly larger within the AVM feeder arteries compared with the corresponding arteries in the contralateral hemisphere (0.14 cm versus 0.12 cm; P=0.0008).…”
Section: Discussionmentioning
confidence: 99%
“…This result reveals that cerebral AVMs are a high WSS pathology, which disputes Rossitti and Svendsen's hypothesis that WSS in arteries supplying AVMs is the same as in arteries within normal brain parenchyma. 12 This difference may be attributed to varying methods of blood flow measurement-Rossitti and Svendsen used TCD, whereas we used QMRA. Indeed, TCD is considered to be highly operatordependent and inferior to QMRA that provides better resolution and 3D localization capability.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, chronic increases in blood flow, and consequently shear stress, lead to the expansion of the luminal radius such that mean shear stress is returned to its baseline level (Kamiya & Togawa, 1980, Girerd et al, 1996. This is clearly demonstrated in the radial artery of dialysis patients proximal to their arteriovenous fistula (Girerd et al, 1996) or in feeder arteries supplying cerebral arteriovenous malformations (Rossitti & Svendsen, 1995), both of which lead to the expansion of the blood vessels calibre as a result of increased shear stress in the vessel lumen. Conversely, decreased shear stress resulting from lower flow or blood viscosity induces a decrease in internal vessel radius (Lowell & O'Donnell, 1986).…”
Section: Blood Flow Shear Stress and Vessel Calibrementioning
confidence: 97%
“…For example, it is well documented that hemodynamic shear stress is a major contributor to IA pathogenesis [14, 15]. Arteriovenous malformations are characteristic of HHT and are thought to be characterized in part by alterations in shear stress [16, 17]. Therefore, one important pathogenic factor that may affect endoglin expression and/or function is hemodynamic stress.…”
Section: Discussionmentioning
confidence: 99%